Kajian Psikosufistik terhadap Penciptaan Manusia dalam Islam - Agus Suyadi Raharusun (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
One of the most important information in the Qur'an and the hadith of the Prophet is the creation of man. One of the Qur'an mentions, that humans are made from the essence of soil (Surah 23:12). Another verse mentions, dry clay from black mud formed (Surah 15:28). This study focuses on tracing the creation of humans through the works of previous researchers that have been published in reputable journals and also books that are in line with research needs. The research approach is qualitative. To unravel the psychological meaning of Sufism, the theory of maqam Nafs Shaykh Hakim Muinuddin Chisyti is used. The results of this study indicate that humans who are in the process of creation to become a baby are in a basic spiritual level, namely the level of the soul or maqam nafs. Babies who are in the womb and who have been born into the world do not have optimal awareness. He can only do something simple according to the fact of his thinking ability.